Influences of initial position on negotiation approach in solving environmental cases in Malaysia - Abdul Rahim, Norhayati Rafida; Bolong, Jusang; Tamam, Ezhar; Osman, Mohd Nizam (Human Resource Management Academic Research Society, 2017)
This article examines the influences of initial position on negotiation approach in solving environmental cases in Malaysia. Negotiation is referred as a tool of solving conflict which is due to different of interest or needs between individuals and groups. Since conflict may be complicated at times, a great number of studies make emphases mainly approaches of negotiation, medium of communication and nature of conflicts and specifically influences on the negotiation approach in solving environmental cases in Malaysia. What is the level of initial position possessed by environmental control officers? What is the type of negotiation approaches employed? Is there any relationship between initial position and negotiation approach used in solving the environmental conflict? The analysis wishes to identify which level of initial position that promotes the negotiation approach in solving environmental cases in Malaysia. A quantitative approaches employed using a survey which adopts a set of questionnaire and responses of 186 respondents are analyzed (when is done?). The analysis includes descriptive, Pearson correlation and Chi-Square test. There is a negative significant correlation between the initial position and the approach of negotiation with a weak correlation. It indicates a reverse influence by which the lower level of initial positive, the more tendencies that the integrative approach of negotiation is employed. The initial position determines how the negotiation is managed which leads to the outcome of negotiation either win-win, win lose or lose-lose. An extensive study may revisit the context of study and the elements of negotiation that determines the success of one negotiation.